189k views
4 votes
When the equation a – bx = cx + d is solved for x, the result is x = StartFraction a minus d Over b plus c EndFraction..

Use the general solution to solve 5 – 6x = 8x + 17.

2 Answers

5 votes

Answer: -6/7

Explanation:

5 - 6x = 8x + 17

-5 -5 <= subtract 5 from both sides

-6 x = 8x + 12

-8x -8x <= subtract -8x from both sides to isolate the variable

-14x = 12

-14 -14 <= divide by -14 to factor out and isolate x

-12/14 can be simplified to -6/7

User Salomonvh
by
6.3k points
2 votes

Answer:

x = -12/14 is the required solution for the given expression.

Explanation:

Here, the given expression is:

5 – 6 x = 8 x + 17

Now, here solving the expression for the value of x, we get:

5 – 6 x = 8 x + 17

⇒ 5 - 17 = 8 x + 6 x

⇒- 12 = 14 x

or, x = -12 / 14

Hence, x = -12/14 is the required solution for the given expression.

User Avraam Mavridis
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.